LITERATURE STUDY OF ADVERTISING ETHICS ON NISSAN MARCH CAR MARKETING AGAINST THE ETHICAL THEORY OF PRODUCTION AND CONSUMER MARKETING - Napoleon Sinaga; Jenni Ferlina Muslim; Mufti Wita Kusuma; Achmad Alfi; Junita Hutabarat; Yani Hendrayani (SEAN Institute, 2023)
Business ethics can broadly be interpreted as provisions regulated by law, even higher standards than the minimum standards of legal provisions, because in business activities we often find gray areas that are not regulated by legal provisions. Ethical behavior in running a business is something essential for the survival of the business itself, because unethical behavior will be harmful, especially when viewed from a long-term perspective. A good business is not only profit-oriented, but a good bus is profitable and has good value morally. The application of business ethics aimed not only at producers but also consumers who use it has been regulated and protected with various laws andregulations to maintain fairness and comfort in transactions. Appliedly, business ethics also highlights the moral aspects of human behavior and regulations that have a profession in business and management. Thus, business ethics can be seen as an attempt to formulate and apply ethical principles in economic relations between people.